PENGARUH PENAMBAHAN SIROP UMBI YAKON (Smallanthus sonchifolius) TERHADAP KANDUNGAN GIZI DAN KADAR VITAMIN B7 PANGAN FUNGSIONAL DADIH SUSU SAPI - Hesti Pembayun (2022)
The prevalence of Type 2 Diabetes Mellitus (T2DM) due to consumption of unhealthy foods continues to increase. The increased diuretic due to the osmotic effect of blood sugar in people with T2DM could cause vitamin deficiency, one of wich is vitamin B7 (biotin). In the case of controlling that event, alternative functional foods were needed. The purpose of this study was to formulate cow's milk dadih with the addition of yacon tuber syrup as an antidiabetic food that helps the vitamin B7 adequacy. In spesific objectives were to analyze the effect of yacon tuber syrup addition on nutrient and vitamin B7 levels in dadih. Single-Factor Completely Randomized Design with repetitions was used as the method. The formula consists F1 (10%), F2 (20%), and F3 (30%) yacon syrup addition. Nutrient and vitamin B7 contents levels were analyzed by One-way Anova and Duncan's Multiple Range Test (DMRT), while the organoleptic (hedonic) data were analyzed by the Kruskal Wallis and Mann Whitney Test. The results showed that yacon syrup affect fat, carbohydrate, and vitamin B7 levels (p<0.05) and did not affect water, ash, and protein level (p>0.05) in dadih. The chosen formula was F3 with a 30% addition of yacon syrup tuber.